2002
DOI: 10.1021/jp0205923
|View full text |Cite
|
Sign up to set email alerts
|

Keto−Enol Isomerization of Gas-Phase 2‘-Methylacetophenone Molecular Ions Probed by High-Temperature Near-Blackbody-Induced Dissociation, Ion−Molecule Reactions, and ab Initio Calculations

Abstract: The thermal dissociation of several substituted acetophenone molecular ions induced by infrared radiation from a hot wire has been studied in a Fourier transform ion cyclotron resonance spectrometer. The temperature dependence of the dissociation rate constants reveals that the 2′-methylacetophenone molecular ion is characterized by a much higher activation energy for dissociation than other acetophenones. This molecular ion also exhibits a very different behavior with respect to charge-transfer reactions. Unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
1
6
0
2
Order By: Relevance
“…Particularly, it was found that keto-enol isomerization is important and involved for ketones. This was, for example, verified by the thermal dissociation of several substituted acetophenone molecular ions studied experimentally and theoretically by Giroldo et al [24]. However, it was assumed that the isomers found in this work hardly contribute to the photodissociation products at the steady state limit.…”
Section: Discussionsupporting
confidence: 73%
“…Particularly, it was found that keto-enol isomerization is important and involved for ketones. This was, for example, verified by the thermal dissociation of several substituted acetophenone molecular ions studied experimentally and theoretically by Giroldo et al [24]. However, it was assumed that the isomers found in this work hardly contribute to the photodissociation products at the steady state limit.…”
Section: Discussionsupporting
confidence: 73%
“…They studied the dissociation of acetophenone molecule ions and found an Arrhenius relationship between the dissociation rate constant and the radiation temperature of the heated filament (log e k diss versus 1/T rad ) which was varied over a range from 910 to 1700 K. From modeling these data, they were able to obtain a value for the threshold dissociation energy which fit within the wide range of values that had been measured previously with other methods [24]. Subsequent work by Sena and Riveros examined the keto-enol isomerization of acetophenone [25] and 2 -methylacetophenone molecular ions [26] using this method. The threshold dissociation energy for loss of methyl from the molecular ion of p-cymene has also been obtained from this filament dissociation method [27].…”
Section: Introductionmentioning
confidence: 87%
“…Near blackbody radiation can be obtained using a heated filament, and several implementations have used a heated filament as a source of photons for dissociation [24][25][26][27][28][29]. This technique has the advantage of being a pulsed method, like IRMPD and a broadband photon source similar to BIRD.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some studies based on acid-base properties in solution of methyl-substituted acetophenones were made in order to elucidate the steric effects of ortho substituents on their basicities [2]. Keto-enol isomerisation of gas-phase 2 0 -methylacetophenone has been the subject of a study made by Giroldo and Riveros [3]. They studied the thermal dissociation of some substituted acetophenones, characterizing both the fragment ion produced in the dissociation and the molecular ion undergoing dissociation and identified the structures of molecular ions.…”
Section: Introductionmentioning
confidence: 99%